If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying B = -5A + 26 Reorder the terms: B = 26 + -5A Solving B = 26 + -5A Solving for variable 'B'. Move all terms containing B to the left, all other terms to the right. Simplifying B = 26 + -5A
| 8-6(2x-8)-5x=9-5(3+4x) | | x/16=21/32 | | x-193=54 | | 42+x=179 | | 60x=100-48 | | 9x=80+7 | | -2x^3(9x^3-7x^2+6x)= | | 12x=76 | | 24x=20 | | x/27=23 | | x/21=12 | | x/17=13 | | 3x+-5x-(x+3)=8x+(-5x-9) | | 3(y+2)+5= | | (36x^6-24x^4+16x^3)= | | 1/7x2 | | .16s+.24s+.24s=5.12 | | (16x+60)(8x)=180 | | (h)-3=x^4+3x^2+2 | | 15-2[x+3]=x+9 | | -3=x^4+3x^2+2 | | 0.07y-0.06=15 | | 0.07-0.06=0.15 | | x^2+4xy^2-4x+4y+5=0 | | 6=x/x | | 24/48 | | x+2=7x+9 | | (-2)*(-0.2)*2+(-0.8)= | | 6=7x+9 | | f(6)=7x+9 | | y=28x+32 | | .75x^2-6x=0 |